Місце внутрішньогосподарського контролю в системі управління виробничими запасами на підприємствах - Колісник, Олена Пилипівна; Костенко, Анастасія Сергіївна; Kolisnyk, Olena Pylypivna; Kostenko, Anastasiia Serhiivna (Національний університет «Острозька академія», 2025)
У статті досліджено класифікацію запасів, їхній вплив на фінансову стабільність підприємства та методи внутрішньо господарського контролю. Розглянуто питання внутрішньогосподарського контролю виробничих запасів як ключового елемента управління підприємством. Визначено етапи проведення контролю, його суб’єкти та об’єкти. Окреслено перспективи вдосконалення внутрішнього контролю з урахуванням автоматизації та цифровізації облікових процесів, зокрема за допомогою сучасних підходів до обліку та контролю, з використанням інформаційних технологій (SAP, ERP-систем, RFID)

This article explores the critical role and significance of internal economic control within the production inventory management systems of modern enterprises. Inventories represent a fundamental component of corporate assets, directly influencing production continuity, cost efficiency, and overall financial stability. The study highlights that effective internal control over inventories ensures the rational use of resources, prevents operational shortages or surpluses, and minimizes the risk of financial losses caused by inefficient stock management.The paper analyzes various classifications of inventories based on their purpose, liquidity, and relation to production cycles. It emphasizes that production inventories–comprising raw materials, auxiliary materials, fuel, spare parts, and packaging–serve as the vital foundation for maintaining uninterrupted production processes. The article further defines the objectives, objects, and subjects of internal control, presenting them in a structured framework to demonstrate their interdependence within the broader management system. Special focus is given to control methods, including both documentary techniques (formal, normative, and comparative checks) and factual procedures (inventory counts, observations, and control weighing).Furthermore, the research examines the transformation of internal control processes under the influence of automation and digitalization. The integration of ERP systems, RFID technology, and electronic document management is presented as a modern solution for improving transparency and accuracy. Using the example of Ukrainian enterprises such as the ROSHEN corporation, the study illustrates how innovative control tools increase operational efficiency and strengthen financial security. The article concludes that digital transformation contributes to sustainable business performance and enhances competitiveness in a rapidly changing economic environment
The place of internal economic control in the system of production inventory management at enterprises
Keywords: виробничі запаси; внутрішньогосподарський контроль; запаси; об’єкти; суб’єкти; інвентаризація; production stocks; internal control; inventories; objects; subjects; inventory